Transcontextual Narratives of Inclusion: Mediating Feminist and Anti-Feminist Rhetoric - Ehret, Verna Marina (Religions, 2018)
In seeking a path to mediating feminist and anti-feminist narratives, one must begin with a framework of the method of narrative analysis being used. Using the works of such thinkers as Paul Ricoeur and Richard Kearney, I argue that human self-understanding and therefore sense of identity is narrative dependent. While this idea has its critics, in the framework of the central question of this essay narrative theory is a particularly productive tool. The story that I tell that gives me identity is not only a story about the surface. It is embedded in my being. I do not simply have a story, I am a story and create my world through that story. Narrative is a part of the ontological structure of being human and the ontic experience of being in the world. One narrates one's life not in the sense of a movie voiceover, but rather as a reflective and reflexive understanding of oneself. Kearney's work in Anatheism is particularly useful for this discussion. While Kearney's interest is in the dialectical move from theism to atheism to a synthesis that is an atheist-informed theism, one can see the same trajectory at work in feminism and anti-feminism. If one begins with patriarchy and moves to feminism, the next step becomes anti-feminism informed by feminism. However, there is still room for an additional dialectical move, to regain a feminism that invites in its detractors and reshapes the collective narratives that impact how we interact with each other in community.